2010
DOI: 10.1016/j.childyouth.2009.11.005
|View full text |Cite
|
Sign up to set email alerts
|

A steady presence in the midst of change: Non-kin natural mentors in the lives of older youth exiting foster care

Abstract: The purpose of this study was to explore the nature of the non-kin natural mentoring relationships among 19-year-old youths (N=189) in the process of "aging out" of the foster care system. Data for the present study are from the final interview of a longitudinal study of older youth exiting the foster care system in Missouri. Participants that reported a natural mentoring relationship at age 19 were asked a series of qualitative questions about their reported relationship. The sample in this study was 65% fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 21 publications
6
68
0
1
Order By: Relevance
“…Of note, consistent with our partner Bellefaire Jewish Children's Bureau (see above) and previous research (Munson et al 2010), these young adults articulate a desire to talk with and learn from others like them, others who have shared similar experiences. This research supports previous suggestions that point to the need to implement services with a variety of provider-types, including peers and paraprofessionals (Pringle et al 2010).…”
Section: Intervention Strategy Considerationssupporting
confidence: 75%
“…Of note, consistent with our partner Bellefaire Jewish Children's Bureau (see above) and previous research (Munson et al 2010), these young adults articulate a desire to talk with and learn from others like them, others who have shared similar experiences. This research supports previous suggestions that point to the need to implement services with a variety of provider-types, including peers and paraprofessionals (Pringle et al 2010).…”
Section: Intervention Strategy Considerationssupporting
confidence: 75%
“…Additionally, the extant relationship provides youth with the time they need to build trust as opposed to forcing a matched relationship within the timeline of a formal mentoring program like Big Brothers Big Sisters. For example, Munson et al (2010) interviewed almost 200 emancipating foster youth with natural mentoring relationships and found that the youth characterized positive natural mentoring relationships by their consistency and longevity as well as their qualities related to trust, authenticity, respect, and empathy. For some youth, the relationship with their natural mentor was the longest, most consistent relationship they had experienced.…”
Section: Youth Perspectivementioning
confidence: 98%
“…Although studies on natural mentoring as a protective factor for foster youth are accumulating (e.g., Ahrens et al, 2008Ahrens et al, , 2011Greeson, 2013;Greeson & Bowen, 2008;Greeson et al, 2010;Munson & McMillen, 2009;Munson, Smalling, Spencer, Scott, & Tracy, 2010), none have explicitly examined child welfare professionals' attitudes and beliefs about implementing natural mentoring in child welfare agency settings. Developing such an understanding will help key stakeholders, like child welfare leadership, to create and implement contextspecific natural mentoring programs, particularly within child welfare organizations.…”
Section: The Current Studymentioning
confidence: 98%
“…Qualitative studies suggest that certain characteristics of caring adults are important for a successful mentor relationship, including affirmation, attention, availability, authenticity, companionship, empathy, respect, and trust (e.g., Drapeau, Saint-Jacques, Lépine, Bégin, & Bernard, 2007;Greeson & Bowen, 2008;Hines et al, 2005;Laursen & Birmingham, 2003;Munson, Smalling, Spencer, Scott, & Tracy, 2010;Spencer, 2006). Several studies demonstrate that social support, or the psychological and informational resources available to individuals through their relationships with family, friends, communities, and professionals (House, 1981), is one of the primary ways that mentor relationships may protect atrisk youth (Casey-Cannon, Pasch, Tschann, & Flores, 2006;Greeson & Bowen, 2008;Osterling & Hines, 2006).…”
Section: Resilience and Asset-focused Strategies To Promote Positive mentioning
confidence: 99%